(untitled) (Journal of the College of Basic Education, 2022)
The extrapolation of the concept of (vision) according to the conscious circulation of theorizing movements, and the nature of dealing with the concept in the work process, to analyze its criteria as a (philosophical) concept, works to reproduce the presentation time based on the dialectic of the aesthetic bilateral communication (to form the visual) and the semantic (the mental concept). . To form the tensions dealt with by some researchers in a (self-)interpretation mode, proceeding in extrapolating the concept of (vision), on a group of circulating readings, and according to the (theoretical) context.